The effect of joint orientation on passive movement of the dog’s stifle - Yair, Nadav; Yiapanis, Christos; Ben-Amotz, Ron; Milgram, Joshua (Frontiers in Veterinary Science, 2023)
Introduction The cranial cruciate ligament (CCL) is one of numerous structures which determine the path of the tibia relative to the femur when passively flexing/extending the stifle of the dog. The effect of cutting the CCL on passive motion with the hind limb in different orientations, is unknown. The aim of this study was to describe passive movement of the tibia relative to the femur in dogs, with the hind limb in three different orientations, and with CCL intact and cut. Methods Ten cadaveric hind limbs were obtained from dogs weighing between 20 kg and 25 kg and prepared for testing in a custom-built joint testing machine. Each hind limb was tested in three different orientations with data collected, using an electromagnetic tracking system, during 2 cycles of flexion/extension with the CCL intact and cut. Each cycle was initiated with the stifle in full extension (0°) and data was collected at 0°, 20°, 30°, 40°, 45°, and 55° of stifle flexion/extension. Results Flexion of the stifle resulted in caudal translation and internal rotation of the tibia relative to the femur, with cranial translation and external rotation occurring during extension along the identical path. Cutting the cranial cruciate ligament did not result in significant differences in translation or rotation when the stifle was orientated to approximated the standing position of a dog. Discussion Isometric points at the origin and insertion of the CCL can potentially be identified in CCL deficient stifles using a technique based on passive motion of an intact stifle.